The mechanisms of NLRP3 inflammasome/pyroptosis activation and their role in diabetic retinopathy - Zheng, Xiaoqin; Wan, Jia; Tan, Gang (Frontiers in Immunology, 2023)
In the working-age population worldwide, diabetic retinopathy (DR), a prevalent complication of diabetes, is the main cause of vision impairment. Chronic low-grade inflammation plays an essential role in DR development. Recently, concerning the pathogenesis of DR, the Nod-Like Receptor Family Pyrin Domain Containing 3 (NLRP3) inflammasome in retinal cells has been determined as a causal factor. In the diabetic eye, the NLRP3 inflammasome is activated by several pathways (such as ROS and ATP). The activation of NPRP3 leads to the secretion of inflammatory cytokines interleukin-1β (IL-1β) and interleukin-18 (IL-18), and leads to pyroptosis, a rapid inflammatory form of lytic programmed cell death (PCD). Cells that undergo pyroptosis swell and rapture, releasing more inflammatory factors and accelerating DR progression. This review focuses on the mechanisms that activate NLRP3 inflammasome and pyroptosis leading to DR. The present research highlighted some inhibitors of NLRP3/pyroptosis pathways and novel therapeutic measures concerning DR treatment.